(untitled) (The Proceedings of The International Conference on Climate Change, 2023)
The global climate is changing with attendant devastating consequences on human livelihood and socioeconomic activities. This change has been related to greenhouse gas (GHG) emissions, which primarily include carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O) and are characterised by spatiotemporal fluctuations over the planet. The objective of the research is to analyse temporal variation of greenhouse gases emissions over Nigeria from 2000 - 2021. Data used were obtained from the archive of the Emissions Database for Global Atmospheric Research (EDGAR). This database provides time-series emissions as national totals using international statistics and a consistent Intergovernmental Panel on Climate Change (IPCC) methodology. Monthly data for a period of 21 years covering 2000-2021 were obtained for Nigeria. Trend analysis was carried out on a monthly, seasonal and annual basis to define the historical emissions trend path over Nigeria using descriptive statistics and the Mann-Kendall test. Results of the monthly analysis from January to December for the given historical years demonstrated steady upward trends for two gases namely CO2 and N2O which are significant at the 0.05 alpha levels. On the contrary, the CH4 gas emission indicated different trends for different months which are not significant at the 0.05 degree of alpha. Furthermore, similar scenarios of significant upward trends of CO2 and N2O emissions, but not for CH4 are noticeable with respect to the seasonal and annual time-series. As a result, Nigeria’s Nationally Determined Contributions (NDCs) to the United Nations Framework Convention on Climate Change (UNFCCC) have not resulted in a positive commitment to achieve net-zero emissions by 2060.